2019
DOI: 10.2147/imcrj.s198011
|View full text |Cite
|
Sign up to set email alerts
|

<p>Corneal deposition of fluoroquinolones after penetrating keratoplasty: case series</p>

Abstract: Purpose: To report three cases of fluroquinolone deposition in the cornea after topical administration post-penetrating keratoplasty. Case reports: Herein we report three patients ranging in age from 42–65 years who underwent keratoplasty with cataract extraction, with intraocular lens implantation in the first two cases and left aphakic due to a posterior capsular tear in the third case. The first two patients received ciprofloxacin-dexamethasone combination drops, and devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Its safety and penetration have been studied by Solomon et al 1 Few cases of fluoroquinolone induced toxicity has been reported. 2,3 But only very few cases of Moxifloxacin induced corneal toxicity has been reported in literature till date. 4 Common Side effects following fluoroquinolone use are dry eye, conjunctivitis, irritation and watering all of which were transient and mild.…”
Section: Discussionmentioning
confidence: 99%
“…Its safety and penetration have been studied by Solomon et al 1 Few cases of fluoroquinolone induced toxicity has been reported. 2,3 But only very few cases of Moxifloxacin induced corneal toxicity has been reported in literature till date. 4 Common Side effects following fluoroquinolone use are dry eye, conjunctivitis, irritation and watering all of which were transient and mild.…”
Section: Discussionmentioning
confidence: 99%